The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.4236/mrc.2017.61002
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Novel Complex Nano-Structured Gold Catalyst Au@T<sub>i</sub>O<sub>2</sub>/MCM-22, Characterization and Remarkably Catalytic Performance for Cyclohexane Oxidation

Abstract: A novel complex nano-structured Au@TiO 2 gold catalyst has been prepared. Au precursor could be transformed into Au@TiO 2 /MCM-22 with the complex nano-structured using two different methods. Samples were characterized by XRD, FT-IR, UV-vis, TEM, ICP-AES and N 2 adsorption-desorption. It is found that gold was anchored on the TiO 2 /MCM-22 as small size and uniform particles with the average diameters in the range of 5 -9 nm. Catalytic results show that such nano-gold catalysts display excellent catalytic perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Therefore, designing a suitable catalyst for indole purification is necessary. One of the recent ways for creating such a design is fixing photocatalysts on the surface of zeolites which has been providing an excellent opportunity for improving zeolites efficiency [17][18][19]. For instance, in an experimental study, Mihajlovic et al modified natural zeolite with Fe(III), and found that this way increased the adsorption capacity of the zeolite [20].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, designing a suitable catalyst for indole purification is necessary. One of the recent ways for creating such a design is fixing photocatalysts on the surface of zeolites which has been providing an excellent opportunity for improving zeolites efficiency [17][18][19]. For instance, in an experimental study, Mihajlovic et al modified natural zeolite with Fe(III), and found that this way increased the adsorption capacity of the zeolite [20].…”
Section: Introductionmentioning
confidence: 99%
“…Of late many works have been carried out using molecular oxygen as oxidant and it proves its versatility and superiority over other oxidants [9]. The product of cyclohexane oxidation KA oil is used as a raw material to prepare adipic acid and caprolactum [10]. Of late, the oxidation of cyclohexane to cyclohexanol and cyclohexanone is developed in heterogeneous system.…”
Section: Introductionmentioning
confidence: 99%